A phase I trial of two sequence-specific schedules of decitabine and vorinostat in patients with acute myeloid leukemia. Issue 10 (3rd October 2015) - How, Jonathan; Minden, Mark D.; Brian, Leber; Chen, Eric X.; Brandwein, Joseph; Schuh, Andre C.; Schimmer, Aaron D.; Gupta, Vikas; Webster, Sheila; Degelder, Tammy; Haines, Patricia; Stayner, Lee-Anne; et al.
Abstract : This phase I trial evaluated two schedules of escalating vorinostat in combination with decitabine every 28 days: (i) sequential or (ii) concurrent. There were three dose-limiting toxicities: grade 3 fatigue and generalized muscle weakness on the sequential schedule ( n = 1) and grade 3 fatigue on the concurrent schedule ( n = 2). The maximum tolerated dose was not reached on both planned schedules. The overall response rate (ORR) was 23% (three complete response [CR], two CR with incomplete incomplete blood count recovery [CRi], one partial response [PR] and two morphological leukemic free state [MLFS]). The ORR for all and previously untreated patients in the sequential arm was 13% (one CRi; one MLFS) and 0% compared to 30% (three CR; one CRi; one PR; one MLFS) and 36% in the concurrent arm ( p = 0.26 for both), respectively. Decitabine plus vorinostat was safe and has clinical activity in patients with previously untreated acute myeloid leukemia. Responses appear higher with the concurrent dose schedule. Cumulative toxicities may limit long-term usage on the current dose/schedules.